Implementasi Kegiatan Agroeduwisata Sebelum dan Setelah Covid-19 oleh Anggota Kelompok Wanita Tani di Bina Pertani - Salsabila, Firdianisa; Syarief, Yuniar Aviati; Effendi, Irwan (Suluh Pembangunan : Journal of Extension and Development, 2023)
This research aims to determine the implementation of Agroedutourism activities before and after Covid-19 at KWT Bina Pertani. This research was conducted in Liman Benawi Village, Trimurjo District, Central Lampung Regency. Data collection in this study was carried out in July-August 2022. About 40 members of the KWT Bina Pertani is the respondents of this study. The qualitative approach is used in this research with a case studies as the research method. The results showed that the implementation of activities in Agroeduwisata was divided into 4, namely education on horticulture cultivation, education on making organic fertilizers from rice husks, processing agricultural products, and making handicrafts (souvenirs). Implementation leads to an activity, series of actions, or system of mechanism. Implementation is more than just an activity, but an action that is planned to achieve the objectives or the goals of the activity The implementation of Agroedutourism activities is the activities that exist in Agroedutourism in accordance with the objectives stated in the Agroedutourism Technical Instructions.